Navigating diversity understanding constraints and catalysts for gender and intersectional inclusion in Colombian land, food, and climate policies through discourse analysis - Howland, Fanny; Blanco, Maria; Pierce, Deborah; Lopera, Diana; Buritica, Alex (2024)
This infonote presents Constraints and Catalysts for Gender and Intersectional Inclusion in Colombian Land, Food, and Climate Policies through Discourse Analysis